Analisis Strategi Hotel Padma Bandung Dalam Meningkatkan Kepuasan Konsumen Melalui Fasilitas Dan Layanan - Nasution, Daffa Ulhaq; Safira, Camilla Mumtazah; Juanto, Aldi (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
This study aims to gain an in-depth understanding of the strategies implemented by Padma Hotel Bandung to enhance guest satisfaction through the optimization of its facilities and services. The primary focus is on identifying key elements that contribute to delivering exceptional customer experiences. Employing a qualitative approach, data were collected through semi-structured interviews with department heads including the Front Office Manager, Marketing Manager, and Food & Beverage Manager alongside non-participant observations in key operational areas of the hotel. The findings highlight that high-quality facility management, personalized service delivery, integrated marketing efforts, and effective cross-departmental collaboration are essential components in fostering guest satisfaction. The study reveals that Padma Hotel Semarang’s commitment to maintaining excellent facilities, responding to customer feedback, and reinforcing internal collaboration significantly contributes to a positive guest experience. This research offers valuable insights for hospitality professionals seeking to improve service quality and customer loyalty. The originality of this study lies in its focus on qualitative insights from department heads, providing a deeper understanding of the strategies behind customer satisfaction in a luxury hotel setting.